EEFECTS OF EUTROPHICATION ON THE SIZE AND NUCLEUS OF SYMBIOTIC ZOOXANTHELLAE - Ambariyanto . (JOURNAL OF COASTAL DEVELOPMENT, 1997)
Zooxanthellae (Symbiodinium sp) from the giant clams, Tridacna maxima, were monitored for their responses to ammonium and phosphate addition in the field. Nutrient was added into ponded microatolls at every low tide using Nutrient Dispersal units (NUDs) moored outside the atolls to reach final concentrations of 10 µm for ammonium and 2µm of phosphate. Transmission electron micrograph showed that zooxanthellae size (as the maximum diameter) from nitrogen-treated clams was significantly than those from other treatments (P<0.05). However, the cross sectional area of the nucleus was not significantly affected by the treatment smaller (P>0.05). The results suggests that the condition of zooxanthellae, such as the size of zooxanthellae from giant clams is influenced by relatively small changes in the concentration of nitrogen in the water column.